Sub-Tenon’s versus Topical Anesthesia for Effectiveness of Analgesia During Cataract Surgery: A Systematic Review with Meta-Analysis - Valizadeh G; Duong E; Thang C; White LD (Clinical Ophthalmology)
Ghazal Valizadeh,1,2 Elliot Duong,3 Christopher Thang,2– 4 Leigh D White3,4 1Department of Ophthalmology, Princess Alexandra Hospital, Woolloongabba, Queensland, Australia; 2Faculty of Medicine, University of Queensland, Herston, Queensland, Australia; 3Department of Anesthesia and Perioperative Medicine, Sunshine Coast University Hospital, Birtinya, Queensland, Australia; 4School of Medicine, Griffith University, Birtinya, Queensland, AustraliaCorrespondence: Ghazal Valizadeh, Department of Ophthalmology, Princess Alexandra Hospital, Woolloongabba, Queensland, Australia, Email ghazal.valizadeh@health.qld.gov.auBackground: Sub-Tenon’s and topical anesthesia are the most common anesthetic techniques employed for cataract surgery. The objectives were to compare the effectiveness of intraoperative analgesia between the two techniques.Methods: A systematic review was performed of three databases (MEDLINE, EMBASE, CENTRAL) from inception until August 2023. Included were adult patients undergoing routine cataract surgery with sub-Tenon’s or topical anesthesia. Excluded were studies using systemic medications and complicated surgeries. The primary outcome was intraoperative analgesia assessed by patient reported pain scores. Secondary outcomes were post-operative pain at 30 minutes and 24 hours, patient satisfaction, surgeon satisfaction and complications. Risk of bias was evaluated using the revised Cochrane risk-of-bias tool for randomized trials (RoB 2). Outcomes were statistically assessed with meta-analyses where able.Results: Twelve studies with 1370 patients were included in the meta-analysis. Sub-Tenon’s block provided better intraoperative analgesia with lower pain scores (SMD − 0.53, 95% CI − 0.70 to − 0.36; p < 0.001) which remained significant on subgroup analysis of six studies with uniform pain scales (MD − 0.84, 95% CI − 1.22 to − 0.47; p < 0.001). Instances of severe intraoperative discomfort requiring rescue regional anesthesia were reported with topical anesthesia. While there was no difference in pain scores at 30 minutes or 24 hours post-operatively, higher patient and surgeon satisfaction was found with sub-Tenon’s anesthesia. Serious complications were rare, with a higher reported rate of posterior capsule rupture with topical anesthesia. Only two of fourteen studies were considered an overall low risk-of-bias.Conclusion: Sub-Tenon’s block provides marginally better intraoperative analgesia during cataract surgery over topical anesthesia. Both can be considered effective for uncomplicated cataract surgery.Keywords: sub-Tenon’s, topical anesthesia, regional anesthesia, cataract surgery